2003
DOI: 10.1121/1.1605415
|View full text |Cite
|
Sign up to set email alerts
|

Hearing protection: Surpassing the limits to attenuation imposed by the bone-conduction pathways

Abstract: With louder and louder weapon systems being developed and military personnel being exposed to steady noise levels approaching and sometimes exceeding 150 dB, a growing interest in greater amounts of hearing protection is evident. When the need for communications is included in the equation, the situation is even more extreme. New initiatives are underway to design improved hearing protection, including active noise reduction (ANR) earplugs and perhaps even active cancellation of head-borne vibration. With that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 10 publications
3
63
1
Order By: Relevance
“…We evaluated the performance of an audiometer employing passive attenuation using insert earphones covered by circumaural earcups coupled with real-time monitoring of environmental noise for air-conduction and boneconduction threshold measurement in a natural environment. Double transducer attenuation using insert foam plugs and circumaural earcups produces a significant increase in ambient noise attenuation that may actually exceed typical attenuation for transportable sound booths (Berger, Kieper & Gauger, 2003;Franks, 2001). Results of the current study confirmed statistically and clinically equivalent hearing thresholds as measured in a natural environment versus a sound-treated booth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated the performance of an audiometer employing passive attenuation using insert earphones covered by circumaural earcups coupled with real-time monitoring of environmental noise for air-conduction and boneconduction threshold measurement in a natural environment. Double transducer attenuation using insert foam plugs and circumaural earcups produces a significant increase in ambient noise attenuation that may actually exceed typical attenuation for transportable sound booths (Berger, Kieper & Gauger, 2003;Franks, 2001). Results of the current study confirmed statistically and clinically equivalent hearing thresholds as measured in a natural environment versus a sound-treated booth.…”
Section: Discussionmentioning
confidence: 99%
“…Active noise monitoring provides a measure of quality control. Furthermore, the system can be set to monitor noise levels according to the average attenuation provided by the test setup in a typical group of subjects as opposed to double attenuation values previously reported (Berger, Kieper & Gauger, 2003). By employing these attenuation levels, the software can be programmed to monitor ambient noise levels across octave or interactive levels, according to standards for audiometric test environments (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At and above 2 kHz there is almost no change in attenuation as a function of insertion depth until the fit becomes so poor that depth of insertion is none at all. Except for the NI fitting, the attenuation at and above 2 kHz approaches and is limited by the flanking bone-conduction (BC) pathways to the inner ear (Berger et al, 2003) and thus varies little as insertion depth is increased. A feature of particular interest is the dip in attenuation at 2 kHz for the SI and DI fittings.…”
Section: Resultsmentioning
confidence: 99%
“…One of the advantages of the dual system is that it enables the listener to communicate with the least intrusion from background noise, resulting in better communication. [10] In [11] These organizations sometimes face situations during which, if the rescue and military personnel hear a signal but misinterpret it, they could convey the wrong message to a partner and face capture or even death from their enemy. [8] The purpose of the present study is to find the most sensitive placement of the skull in order to perceive speech through the bone vibrator in various protection methods while being exposed to noise.…”
Section: Introductionmentioning
confidence: 99%